On Nonlinear Boundary Value Problems for Functional Difference Equations with p-Laplacian - Yong Wan; Yuji Liu (Discrete Dynamics in Nature and Society)
Sufficient conditions for the existence of solutions of nonlinear boundary value problems for higher-order functional difference equations with p-Laplacian are established by making of continuation theorems. We allow f to be at most linear, superlinear, or sublinear in obtained results.